2015
DOI: 10.1097/inf.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors and Molecular Characteristics of Meningococcal Carriage Among Brazilian Adolescents

Abstract: The evidence gathered during this study provides estimates of carriage prevalence in Brazilian adolescents, showing an unusually high dominance of serogroup C. These results have important implications in future strategies to optimize the impact of the current meningococcal C vaccination program in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 27 publications
11
39
1
6
Order By: Relevance
“…meningitidis group C was 0.17%. The overall prevalence for adolescents in Salvador was lower than the prevalence (9.9%) observed in a similar study performed in Campinas, Brazil, after introducing the MCC vaccine among children <2 years old [15]. Moreover, our results were similar to those of studies from other Latin American countries, such as Colombia (6.85%) [20] and Chile (6.5%) [21].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…meningitidis group C was 0.17%. The overall prevalence for adolescents in Salvador was lower than the prevalence (9.9%) observed in a similar study performed in Campinas, Brazil, after introducing the MCC vaccine among children <2 years old [15]. Moreover, our results were similar to those of studies from other Latin American countries, such as Colombia (6.85%) [20] and Chile (6.5%) [21].…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, even though meningococcal carriage is an age-dependent phenomenon (increasing from 4.5% in infants to 23.7% in 19 year olds and then decreasing to 7.8% in adults over 50 years old [23]), we did not find any age-related difference in the carriage prevalence among adolescents 11–19 years old, results that are similar to those found in Campinas [15]. In addition, even though men are the most prevalent meningococcal carriers worldwide [13], sex was not associated with meningococcal carriage in our study [15, 20].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The introduction of the MenC vaccine in Brazil in 2010 provided an immediate reduction in incidence rates of MD, especially in those children targeted for vaccination ( Figure 1). Carriage rates in adolescents, in a study performed 2 years after the initiation of the infant immunization program, showed a prevalence of 10%, where serogroups were identified, serogroup C was the most common (1.32%), followed by serogroups B (0.99%), E (0.74%), Y (0.49%), and W (0.25%) [37]. Although plain PSVs offered protection against disease, they did not prevent acquisition of carriage of MenC in the 2010 outbreaks [38], which is why only conjugate vaccines are now used to control outbreaks.…”
Section: Latin Americamentioning
confidence: 99%